Evidencing nickel biosorption capacity of cyanobacteria Chroococcidiopsis sp.: potential metallo-protective agents - Hadjira Hamai-Amara; Imen Saadaoui; Maroua Cherif; Dana A. Da’ana; Lama Soubra; Mohammad A. Al-Ghouti (BMC Chemistry)
Abstract The increasing prevalence of toxic elements such as nickel (Ni) in the environment poses a significant threat to human health due to its carcinogenic effect. The study investigates the Ni biosorption potential of three cyanobacteria strains: Euhalothece sp., Halospira sp., and Chroococcidiopsis sp. Hence, the physicochemical properties of biomass and extract were assessed through transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), and Brunauer-Emmet-Teller (BET). Batch experiments for Ni2⁺ biosorption were conducted and residual nickel (Ni2⁺) levels were quantitatively assessed using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). The results evidence interesting Ni2⁺ removal efficiency of Chroococcidiopsis sp. biomass reaching a biosorption capacity of 18.19 mg g−1 under pH 6, and 37 °C. Several functional groups including amide, carbonyl, phosphate, and carboxyl groups were revealed as key players in this process via FTIR. Finally, such findings highlight the significant potential of cyanobacterial biomass and by-products to reduce nickel bioavailability to prevent Ni-induced carcinogenesis. Graphical Abstract